Effect of PreAnaesThesia Computerized Health (PATCH) assessment on duration of nurse-patient consultation and patient experience : a pilot trial - Osman, Tarig (2021)
Preanaesthesia health assessment is gradually transitioning from paper-based, face-to-face assessment to digitized assessment, self-administered by the patient. This transition could potentially optimize the various goals of assessment, notably facilitating the efficient collection of the patient’s health information. We have previously developed and validated a tablet application (PreAnaesThesia Computerized Health assessment application or “PATCH”) for patients to conduct preanaesthesia self-assessment. In a randomized controlled trial, we sought to compare the duration of nurse–patient consultation and patient satisfaction between patients who underwent PATCH self-assessment vs. standard care nurse-led assessment. Fifty-two elective surgical patients were randomized to complete either PATCH assessment or standard care nurse-led assessment at an outpatient preoperative clinic. The duration of nurse–patient consultation was subsequently noted for all patients who also completed a satisfaction survey. The mean (SD) nurse–patient consultation times in the PATCH and standard care groups were comparable, at 11.5 (3.6) min and 12.2 (2.9) min, respectively (p = 0.703). Overall satisfaction scores were also comparable, at 23.9 and 27.0 respectively (p = 0.451) for the PATCH and standard nurse assessment groups. Favorable perceptions of PATCH among users ranged between 41.7% and 79.2%. In conclusion, PATCH self-assessment can feasibly be introduced into current practice with comparable nurse–patient consultation times and patient satisfaction.